Analisis Mutu Sensoris, Fisik dan Kimia Biskuit Balita Yang Dibuat Dari Campuran Tepung MOCAF (Modified Casavva Flour) dan Wortel (Daucus carota) - Anasthasia K. Mamentu; Erny Nurali; Tineke Langi; Teltje Koapaha (COCOS, 2013)
ABSTRACTThis research aims to produce biscuits toddler with the addition of carrot pulp concentration that can be accepted by panelists from both physical and chemical properties. This research using completely randomized design with treatment mocaf flour mixture and pureed carrots. Treatment A=(85% MOCAF flour: 15% carrot pulp), B=(80% MOCAF flour: 20% carrot pulp) C=(75% MOCAF flour: 25% carrot pulp) D=( 70% MOCAF flour: 30% carrot pulp) E= (65% MOCAF flour: 35% carrot pulp). The chosen of produced by sensory, is going with the analysis of sensory physical and chemical . the chosen of toddler biscuitsis the treatment E=(65% MOCAF flour: 35% carrot pulp). results of the analysis of physical and chemical biscuits toddlers is content of chemicals are activity water 5.25%, ash 2,60%, fat 25,65%, protein 8.83%, dietry fiber 0.18% and karbohidrat 57,48. For component of Vitamin A is 1607.5 IU and energy total is 496,09 Kkal.Keywords: biscuits, MOCAF, carrot